Decision Support System for Receiving Family Hope Program (PKH) Assistance in Mandalahayu Village, kab. Tasikmalaya - Yuda Purnama Putra; Egi Badar Sambani; Ade Taopik Hidayatuloh; Czuko Adiwiputra (Politeknik Mardira Indonesia, 2024)
Program Keluarga Harapan (PKH) is a government policy related to the empowerment of poor families. The program aims to accelerate poverty reduction in an integrated and sustainable manner. In choosing beneficiaries, there are often problems, one of which is that the beneficiaries are not right on target based on government regulations. In practice, officers at the Mandalahayu Village Office use simple grouping of data to determine the eligibility of beneficiaries and tend to be long. To simplify and speed up the entire process, a decision support system was created using the Simple Additive Weighting (SAW) method. The concept of the Simple Additive Weighting method is to find the weighted sum of each alternative's performance rating on all attributes. This system is expected to be a solution in determining beneficiaries so that it is right on target. The programming language used in this system is Pear Hypertext Preprocessor (PHP), coupled with Cascading Style Sheet (CSS) to make it look more attractive. Data storage uses MySQL as a Database Management System, and JavaScript as a supporting display to make it more interactive